Long COVID awareness and receipt of medical care: a survey among populations at risk for disparities - Fisher, Kimberly A.; Mazor, Kathleen M.; Epstein, Mara M.; Goldthwait, Lydia; Abu Ghazaleh, Hiba; Zhou, Yanhua; Crawford, Sybil; Marathe, Jai; Linas, Benjamin P. (Frontiers in Public Health, 2024)
The COVID-19 pandemic has been characterized by disparities in disease burden and medical care provision.Whether these disparities extend to long COVID awareness and receipt of medical care is unknown. We aimed to characterize awareness of long COVID and receipt of medical care for long COVID symptoms among populations who experience disparities in the United States (US).We conducted a cross-sectional survey among a national sample of US adults between January 26-February 5, 2023. We surveyed approximately 2,800 adults drawn from the Ipsos probability-based KnowledgePanel® who identify as White, Black, or Hispanic, with over-sampling of Black, Hispanic, and Spanish-proficient adults.Awareness of long COVID was assessed with the question, "Have you heard of long COVID? This is also referred to as post-COVID, Long-haul COVID, Post-acute COVID-19, or Chronic COVID". Respondents reporting COVID-19 symptoms lasting longer than one month were classified as having long COVID and asked about receipt of medical care.Results: Of the 2,828 respondents, the mean age was 50.4 years, 52.8% were female, 40.2% identified as Hispanic, 29.8% as Black, and 26.7% as White. 18% completed the survey in Spanish. Overall, 62.5% had heard of long COVID. On multivariate analysis, long COVID awareness was lower among respondents who identified as Black (OR 0.64; 95% CI 0.51, 0.81), Hispanic and completed the survey in English (OR 0.59; 95% CI 0.46, 0.76), and Hispanic and completed the survey in Spanish (OR 0.31, 95% C.I. 0.23, 0.41), compared to White respondents (overall p <.001). Long COVID awareness was also associated with educational attainment, higher income, having health insurance, prior history of COVID-19 infection, and COVID-19 vaccination. Among those reporting symptoms consistent with long COVID (n = 272), 26.8% received medical care. Older age, longer symptom duration and greater symptom impact were associated with receipt of medical care for long COVID symptoms. Of those who received care, most (77.8%) rated it as less than excellent on a 5-point scale.Discussion: This survey reveals limited awareness of long COVID and marked disparities in awareness according to race, ethnicity, and language. Targeted public health campaigns are needed to raise awareness.